Anti-inflammatory and anticancer properties of Alcea rosea extracts: Insights from in vitro and in vivo studies - Parry, Ruhban Ansar; Wani, Sajad Hamid; Mir, Irfan Ahmad; Bhat, Basharat Ahmad; Hussain, Mahboob Ul; Mir, Mushtaq Ahmad; Bashir, Nasreena; Fadul, Abdalla N.; Jangra, Surender; Vats, Sharad; Ganie, Showkat Ahmad (Frontiers in Pharmacology, 2025)
BackgroundInflammation plays a critical role in colon carcinogenesis by dysregulating multiple signalling pathways. Targeting these inflammatory pathways is essential for effective colorectal cancer management. This study aims to investigate how Alcea rosea L. extracts can prevent inflammation-related colorectal cancer both in vitro and in vivo.MethodsAnti-inflammatory assays were conducted using standard protocols. Anticancer activity was evaluated by MTT assay, while protein expression was analysed via Western blotting. Metabolite identification was performed using GC-MS analysis. In vivo experiments were carried out in BALB/c mice, including histopathological evaluations and biochemical assays, to assess the physiological and molecular effects of the extracts. All experimental procedures followed established scientific guidelines to ensure accuracy and reliability of the results.ResultsIn vitro assays revealed that Alcea rosea extracts inhibited protein denaturation, nitric oxide production, and membrane hemolysis with IC50 values ranging from 47.46 to 268.46 μg/mL. MTT assays demonstrated potent cytotoxicity against HCT116 (IC50 = 30.94 μg/mL), HT29 (IC50 = 46.89 μg/mL), and SW480 (IC50 = 63.40 μg/mL) cell lines. The extracts significantly downregulated COX-2, NFκB, and PPAR-γ protein levels and induced PARP and Caspase 3 cleavage. GC-MS analysis identified anti-inflammatory and anticancer metabolites, including kaempferol derivatives, α-Tocopherol, and phytol. In vivo, AR-EA and AR-Met extracts attenuated LPS-induced paw edema and restored altered biochemical parameters in mice models, highlighting the extracts’ therapeutic potential against inflammation-associated colorectal cancer.ConclusionThe findings highlight the therapeutic potential of Alcea rosea extracts as natural anti-inflammatory and anticancer agents, offering a promising avenue for purification of metabolites which can be utilised for the prevention and management of inflammation-associated colorectal cancer.